A numerical H Darrieus hydrokinetic turbine performance assessment with the application of openings in blade geometry - Gomez, Mateo Arrieta; Muñoz, Angie Guevara; Zuluaga, Diego Hincapie (Center of Biomass & Renewable Energy (CBIORE), 2025)
This study explores the impact of various geometric modifications, including leading-edge openings, trailing- edge openings, and circular openings, on the performance of the H Darrieus hydrokinetic turbine. These modifications involved the removal of material from a symmetrical NACA0018 airfoil along its surface. The leading edge and trailing edge openings extended from the lower to the upper surface of the blade, while the circular opening was applied exclusively to the upper surface. Using the commercial software ANSYS® V22.2, the turbine was designed, discretized, and analyzed through computational fluid dynamics employing the Realizable K-e turbulence model. The primary output variable measured was torque, from which the power coefficient for each design modification was derived, allowing for the calculation of efficiency in each scenario. Notably, the configuration featuring the upper circular opening achieved the highest efficiency at 51.88% at a Tip Speed Ratio (TSR) of 2.0, a significant improvement over the standard case which had an efficiency of 45.16%. In contrast, the leading-edge and trailing-edge openings resulted in reduced efficiencies of 44.54% and 31.19%, respectively. The enhanced power coefficient of the H Darrieus hydrokinetic turbine with circular openings is attributed to the increased pressure difference generated between the upper and lower surfaces of the blade, surpassing the performance of the standard design.